Improving the use of Information and Communication Technology (ICT) in the University of Nicosia in Cyprus through the identification and implementation of appropriate international best practice - Dimitriou, Maria (2016)
"The pace of modern life and the rising of technological advancements and resources result in numerous revolutions in our daily routines, transforming them into a digitised world (Oliver, 2002). In fact, the phenomenon of Information and Communication Technologies (ICT) as the computer infrastructures and telecommunication services that empower users to process and store data and enable access to numerous networks, have completely influenced and renovated all the diverse fields in the industrial ecosphere, including the Higher Educational System (American Library Association,1983). The advent of ICT and the massive effects emerging through it have been investigated by a large number of researchers. More precisely, according to Toro and Joshi (2012), the sphere of ICT is classified as a remarkable tool that enriches the access to global information and communication. While ICT enhances the entry to worldwide collaboration, it also provides an enhanced educational quality, such as in learning and evaluation procedures through the use of technological tools. Nevertheless, the application of ICT has not only assisted the academic practices of Higher Educational Institutions, but it has simultaneously automated and enriched administrative procedures as well, such as the administration of student and staff records, the procurement management and payroll (Ben- Zion Barta et.al.,1995; Zainally,2008; Fu,2013). On the other hand, while the phenomenon of ICT has provided extensive benefits to Higher Education, a number of barriers and challenges have been examined as well in the established literature, including policy strategies, environmental and cultural challenges and educational issues. In fact, the great awareness that scientists have raised in the area of ICT and more precisely in its implementation in Higher Education, as well as the great need of examining the new technological advancements have triggered my interest to study this topic. This study aims to investigate and analyse the application of ICT at the University of Nicosia (UNic) in Cyprus, both for academic and administrative practices. Through the review of four chosen global Universities, an assessment and contrast between each of them and UNic will aid in classifying the weak and strong points of ICT employment at UNic. Subsequently, this will guide the researcher to propose specific recommendations to various problems, for a more effective and enhanced use of ICT at this University. 2 To examine the phenomenon of ICT application at UNic, a mixed methods research was employed, denoting that both qualitative and quantitative data were gathered. As regards the qualitative data, interviews were the data collection tool; more precisely, a total of 11 academic and administrative staff members were interviewed regarding their views towards the ICT at UNic. Among the main findings of the qualitative research was the composition of the framework of UNic’s ICT, showing the available Information Systems and services. Additionally, the enthusiasm of the interviewed administrative staff towards potential updates and modifications of their current Information Systems, despite their limited computer education, was also a major finding of this study. The online questionnaire, as the quantitative data collection method, was responded by 30 current students of UNic expressing their insights regarding the available Student Information Systems. The fundamental results emerging through the experiment were the following: the ‘Student Intranet’ was entitled with a 73.3% as the system that requires the most updates to become more efficient, as well as with a 2.33% mean as the one with the highest number of errors. It is acknowledged that the study was conducted under certain limitations; importantly, time limitations considerably constrained the process of conducting interviews to current staff at UNic, whereas space limitations restricted further elaboration."